2014
DOI: 10.1128/jcm.00290-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of sil Locus in Clinical Streptococcus pyogenes Strains

Abstract: Streptococcus pyogenes (group A Streptococcus [GAS]) causes a wide variety of diseases, ranging from mild noninvasive to severe invasive infections. Mutations in regulatory components have been implicated in the switch from colonization to invasive phenotypes. The inactivation of the sil locus, composed of six genes encoding a quorum-sensing complex, gives rise to a highly invasive strain. However, studies conducted on limited collections of GAS strains suggested that sil prevalence is around 15%; furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…However, our analysis also indicates that the sil locus is not likely operational in MGAS8232 given the apparent truncation of silD . Interestingly, and as previously noted, most strains of S. pyogenes actually lack the majority of the sil locus38; however, other than S. pyogenes M1 serotypes which contain an 11-bp deletion resulting in a frame-shift mutation within the spbM coding sequence [e.g. strains SF37039, MGAS500540 and M1_47641], most sequenced S. pyogenes strains contain complete spbM and spbN sequences.…”
Section: Discussionsupporting
confidence: 53%
“…However, our analysis also indicates that the sil locus is not likely operational in MGAS8232 given the apparent truncation of silD . Interestingly, and as previously noted, most strains of S. pyogenes actually lack the majority of the sil locus38; however, other than S. pyogenes M1 serotypes which contain an 11-bp deletion resulting in a frame-shift mutation within the spbM coding sequence [e.g. strains SF37039, MGAS500540 and M1_47641], most sequenced S. pyogenes strains contain complete spbM and spbN sequences.…”
Section: Discussionsupporting
confidence: 53%
“…The studies done by the French National Reference Center for Streptococci and Chen and al. linked this type of emm to invasive GAS infections (25,26). However, other studies showed that emm90 was involved in a severe epidemic of GAS pharyngitis (7,16).…”
Section: Discussionmentioning
confidence: 99%
“…The sil locus is regulated by quorum-sensing, and the SilCR autoinducing peptide can be sensed across multiple streptococcal species (i.e., SDE) (Belotserkovsky et al, 2009). However, any involvement of sil in DNA transfer involving GAS is unlikely to be a universal mechanism because the sil locus is present in only a minority of GAS strains (Plainvert et al, 2014). …”
Section: Molecular Mechanisms Underlying Genetic Changementioning
confidence: 99%